2014
DOI: 10.1002/ppap.201300200
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation on the Production of Reactive Oxygen Species in Atmospheric Pulse-Modulated RF Discharges with He/O2 Mixtures

Abstract: By choosing an appropriate duty cycle and modulation frequency, the pulse-modulated RF discharge can be optimized to provide a high-density atmospheric plasma with a reduced power consumption but without the risk of gas heating in pure helium. In this paper, we presented a fluid model to investigate the generation of reactive oxygen species (ROS) in an atmospheric pulse-modulated RF discharge with He/O 2 mixtures. The numerical results show that modulated by a pulse the electrons could not fully interact with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…These relatively high emissions from the oxygen species were observed without admixing any external oxygen content to the main discharge gas, which is usually obtained by gas admixture. [ 30,41 ] Electron impact excitation of ground‐state molecular and atomic oxygen leads to the emission at 844.6 and 777.4 nm, which is predicted by the dissociative excitation, given as, e+normalO2e+normalO*+O and direct impact excitation mechanisms, e+Oe+normalO*, where O * refers to the O (3p 5 P) state, which emits at 777.4 nm, and the O (3p 3 P) state, which emits at 844.6 nm. [ 48–50 ] The generation of oxygen metastable is predominantly caused by electron impact dissociation of O 2 , and electron‐induced processes dominate the generation of ground‐state atomic oxygen.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These relatively high emissions from the oxygen species were observed without admixing any external oxygen content to the main discharge gas, which is usually obtained by gas admixture. [ 30,41 ] Electron impact excitation of ground‐state molecular and atomic oxygen leads to the emission at 844.6 and 777.4 nm, which is predicted by the dissociative excitation, given as, e+normalO2e+normalO*+O and direct impact excitation mechanisms, e+Oe+normalO*, where O * refers to the O (3p 5 P) state, which emits at 777.4 nm, and the O (3p 3 P) state, which emits at 844.6 nm. [ 48–50 ] The generation of oxygen metastable is predominantly caused by electron impact dissociation of O 2 , and electron‐induced processes dominate the generation of ground‐state atomic oxygen.…”
Section: Resultsmentioning
confidence: 99%
“…[ 23 ] In another finding, He et al presented a fluid model to investigate the generation of reactive oxygen species in an atmospheric pulse‐modulated RF discharge with He/O 2 mixtures by varying the duty cycle from 30 to 60% at a low modulation frequency <50 kHz. [ 30 ] They also found that the electron density in a pulse‐modulated RF discharge even becomes more significant than that in a continuous RF discharge at some duty cycles (30–60%).…”
Section: Introductionmentioning
confidence: 98%
“…Actually, it is well accepted in MD simulations to ensure adequate reactivity of the whole molecular system in such a small computational domain. [ 27 ] Before the particle impacts, the system is equilibrated at room temperature (300 K) for 50 ps in the NVT ensemble (a constant number of atoms under a constant volume and constant temperature system) using the Berendsen thermostat. The velocity directions of reactive species are chosen randomly.…”
Section: Computational Methods and Simulation Detailsmentioning
confidence: 99%
“…Usually, the ROS density in the simulation domain is much larger than the true density generated in the experimental plasmas. [8][9][10]42] Actually, it is well accepted in MD simulations to ensure adequate reactivity of the whole molecular system in such a small computational domain. Periodic boundary conditions are applied in all three directions to mimic a larger system in our simulations.…”
Section: Simulation Setupmentioning
confidence: 99%
“…[1][2][3][4] A large number of experiments have demonstrated the effect of low-temperature plasma treatment in applications ranging from decontamination of medical equipment and disinfection of tissue to the regeneration of chronic wounds and even cancer treatment, [5][6][7] and the reactive oxygen species (ROS) and reactive nitrogen species (RNS) produced in atmospheric plasmas are believed to play essential roles in plasma medicine. [1,[8][9][10][11] Moreover, the plasma-activated solution (PAS) has attracted increasing attention as a promising tool in plasma medicine, even showing therapeutic effects in cancer treatment, [7,12] which have suggested some differences from the direct cold plasma treatment. [13] PAS can be carried to places where plasma generation is not possible, such as in small organs that are difficult to reach.…”
Section: Introductionmentioning
confidence: 99%